EVALUASI KINERJA SOSIAL EKONOMI DAS BRANTAS BERDASARKAN PENERAPAN P61/MENHUT-II/2014 - Nur Ainun Jariyah (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2019)
Brantas watershed is determined as a national priority watershed to be managed. Brantas watershed is the most critical watershed with various complex problems compared to other 29 watersheds in Java. So that, it becomes a national problem which needs to be solved. This article aims to (a) evaluate Brantas watershed management system to find out its performance, which can be used as an input for watershed management policies and planning, (b) develop better and more efficient Brantas watershed management policy recommendations. The method used the Regulation of the Minister of Forestry of the Republic of Indonesia No. P.61/Menhut-II/2014. The data used are secondary data obtained from Central Agency of Statistics, Brantas Watershed Management Center, Forestry Service, and Social Service. The results showed that Brantas watershed is in good condition, however, some important issues should be addressed, namely population density and the classification of high water building values. Some actions that need to be carried out by the Government, among others (1) finding out other alternative outside the agricultural sector to overcome the high population pressure, (2) necessary maintenance of the functions of recharge areas and water sources to reduce sedimentation in water building